The Mycotoxin Beauvericin Exhibits Immunostimulatory Effects on Dendritic Cells via Activating the TLR4 Signaling Pathway - Yang, Xiaoli; Ali, Shafaqat; Zhao, Manman; Richter, Lisa; Schäfer, Vanessa; Schliehe-Diecks, Julian; Frank, Marian; Qi, Jing; Larsen, Pia-Katharina; Skerra, Jennifer; Islam, Heba; Wachtmeister, Thorsten; et al. (Frontiers in Immunology, 2022)
Beauvericin (BEA), a mycotoxin of the enniatin family produced by various toxigenic fungi, has been attributed multiple biological activities such as anti-cancer, anti-inflammatory, and anti-microbial functions. However, effects of BEA on dendritic cells remain unknown so far. Here, we identified effects of BEA on murine granulocyte–macrophage colony-stimulating factor (GM-CSF)-cultured bone marrow derived dendritic cells (BMDCs) and the underlying molecular mechanisms. BEA potently activates BMDCs as signified by elevated IL-12 and CD86 expression. Multiplex immunoassays performed on myeloid differentiation primary response 88 (MyD88) and toll/interleukin-1 receptor (TIR) domain containing adaptor inducing interferon beta (TRIF) single or double deficient BMDCs indicate that BEA induces inflammatory cytokine and chemokine production in a MyD88/TRIF dependent manner. Furthermore, we found that BEA was not able to induce IL-12 or IFNβ production in Toll-like receptor 4 (Tlr4)-deficient BMDCs, whereas induction of these cytokines was not compromised in Tlr3/7/9 deficient BMDCs. This suggests that TLR4 might be the functional target of BEA on BMDCs. Consistently, in luciferase reporter assays BEA stimulation significantly promotes NF-κB activation in mTLR4/CD14/MD2 overexpressing but not control HEK-293 cells. RNA-sequencing analyses further confirmed that BEA induces transcriptional changes associated with the TLR4 signaling pathway. Together, these results identify TLR4 as a cellular BEA sensor and define BEA as a potent activator of BMDCs, implying that this compound can be exploited as a promising candidate structure for vaccine adjuvants or cancer immunotherapies.